2015
DOI: 10.1007/s11747-015-0428-7
|View full text |Cite|
|
Sign up to set email alerts
|

Life could be so easy: the convenience effect of round price endings

Abstract: Retailers are increasingly using round prices, a trend at odds with the marketing belief in the superiority of just-below prices. However, conclusive empirical evidence on the effectiveness of different price endings is still missing. Addressing this void, this paper presents four fieldexperimental studies with a broad array of samples revealing the central role of convenience in the context of price endings. Findings indicate that consumers perceive round prices as more convenient because their high cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 104 publications
2
30
1
Order By: Relevance
“…In order to assess if the format of the price influences the depth of quantity discounts and incidence of quantity surcharges, each price was categorized as either even (e.g., $20.00), odd (e.g., $19.95, $19.98, $19.99), or irregular (e.g., $17.63), consistent with the standards used in earlier studies on price endings (Manning and Sprott ; Schindler and Kirby ; Stiving and Winer ; Wieseke, Kolberg, and Schons ). It is important to note that the designation of a price as “odd” is consistent with the terminology used in the price‐ending literature and simply reflects the fact that the price is just below round values, not necessarily that it is numerically an odd figure (Estelami ; Wieseke, Kolberg, and Schons ). In total, 48.3% of the prices were irregular, 49.6% were odd, and 2.1% were even.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to assess if the format of the price influences the depth of quantity discounts and incidence of quantity surcharges, each price was categorized as either even (e.g., $20.00), odd (e.g., $19.95, $19.98, $19.99), or irregular (e.g., $17.63), consistent with the standards used in earlier studies on price endings (Manning and Sprott ; Schindler and Kirby ; Stiving and Winer ; Wieseke, Kolberg, and Schons ). It is important to note that the designation of a price as “odd” is consistent with the terminology used in the price‐ending literature and simply reflects the fact that the price is just below round values, not necessarily that it is numerically an odd figure (Estelami ; Wieseke, Kolberg, and Schons ). In total, 48.3% of the prices were irregular, 49.6% were odd, and 2.1% were even.…”
Section: Resultsmentioning
confidence: 99%
“…Research in behavioral pricing shows that the use of specific price formats inhibits computational abilities of consumers (Bhattacharya, Holden, and Jacobsen 2012;Estelami 1999Estelami , 2003Wieseke, Kolberg, and Schons 2016). Cognitive tasks such as division and multiplication become significantly more demanding when price is communicated using irregular figures that cannot be rounded (e.g., $167), compared to when they are round (e.g., $200) or can be easily rounded (e.g., $198, $199).…”
Section: Effects Of the Price Formatmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of studies claim that not only price discount has a certain impact on customer perception, but also the frame − in percentage (relative) or monetary (absolute) terms discount is presented (Biswas & Graw, 2008;Gamliel & Herstein, 2011;Gendall, Hoek, Pope, & Young, 2006). It has been found that framing the same price discount in a different way can influence customer perceptions related to the attractiveness of promotion (Munger & Grewal, 2001;Wadhwa & Zhang, 2015;Wieseke, Kolberg, & Schons, 2016), and may also influence purchase decision (Nusair et al, 2010). Some studies suggest that discount frames result in higher purchase intentions (González et al, 2016), whereas other research indicates that the discount format has no impact on purchase intentions (DelVecchio, Krishnan, & Smith, 2007) or results are mixed (Isabella, Pozzani, Chen, & Gomes, 2012;McKechnie, Devlin, Ennew, & Smith, 2012).…”
Section: Introductionmentioning
confidence: 99%